2023
DOI: 10.3390/fermentation9040319
|View full text |Cite
|
Sign up to set email alerts
|

Third Generation Lactic Acid Production by Lactobacillus pentosus from the Macroalgae Kappaphycus alvarezii Hydrolysates

Abstract: The evaluation of macroalgae as a new raw material for diverse bioprocesses is of great interest due to their fast growth rate and low environmental impact. Lactic acid has a high value in the bio-based industry and is mainly produced via fermentation. The anaerobic lactic acid fermentation of Kappaphycus alvarezii hydrolysates using the high-producing strain Lactobacillus pentosus was evaluated for detoxified and non-treated hydrolysates prepared from concentrated algal biomass and dilute acid solution mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…When using higher biomass concentrations in more prolonged hydrolysis procedures, higher galactose concentrations can be obtained. As shown by Khambhaty et al [72] and Tabacof et al [24], more than 50 g/L of galactose can be reached in a mixture with about a 30% (w/v) biomass concentration. The hydrolysis conditions in these cases were 100-110 • C and 1% (v/v) sulfuric acid concentration, and the hydrolysis time was 45 to 60 min long.…”
Section: Processing K Alvarezii Biomass For Fermentation Processesmentioning
confidence: 87%
See 4 more Smart Citations
“…When using higher biomass concentrations in more prolonged hydrolysis procedures, higher galactose concentrations can be obtained. As shown by Khambhaty et al [72] and Tabacof et al [24], more than 50 g/L of galactose can be reached in a mixture with about a 30% (w/v) biomass concentration. The hydrolysis conditions in these cases were 100-110 • C and 1% (v/v) sulfuric acid concentration, and the hydrolysis time was 45 to 60 min long.…”
Section: Processing K Alvarezii Biomass For Fermentation Processesmentioning
confidence: 87%
“…Using similar conditions with an even higher biomass concentration of 50% (w/v) mix, Hargreaves et al [22] reached a galactose concentration of 82 g/L. The work carried out by Hargreaves et al [22] and Tabacof et al [24,73] showed that exposing K. alvarezii biomass to prolonged acid hydrolysis results in the formation of 1 g/L of HMF for every 4 g/L of galactose.…”
Section: Processing K Alvarezii Biomass For Fermentation Processesmentioning
confidence: 94%
See 3 more Smart Citations